An optical chopper for generation of short X‐ray pulses to allow in‐house time‐resolved photocrystallography. Corrigendum. (1st February 2015) - Kamiński, Radosław; Benedict, Jason B.; Nottingham, Gary; Coppens, Philip
<x xml:space="preserve">Abstract</x> In the paper by Kamiński et al. [J. Appl. Cryst. (2014), 47, 17651768], Jason B. Benedict is missing from the list of authors. The complete list of authors should be Radosław Kamiński, Jason B. Benedict, Gary Nottingham and Philip Coppens.